Bosonic lasers: The state of the art (Review Article) - Kavokin, Alexey; Liew, Timothy C.H.; Schneider, Christian; Höfling, Sven (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Bosonic lasers represent a new generation of coherent light sources. In contrast to conventional, fermionic, lasers they do not require inversion of electronic population and do not rely on the stimulated emission of radiation. Bosonic lasers are based on the spontaneous emission of light by condensates of bosonic quasi-particles. The first realization of bosonic lasers has been reported in semiconductor microcavities where bosonic condensates of exciton-polaritons first studied several decades ago by K.B. Tolpygo can be formed under optical or electronic pumping. In this paper we overview the recent progress in the research area of polaritonics, address the perspective of realization of polariton devices: from bosonic cascade lasers to spin transistors and switches.